Pengaruh Pembelajaran Daring terhadap Tingkat Stres Orang Tua dalam Mendampingi Anak Sekolah Dasar Selama Pandemi Covid-19 di SD Kreatif Muhammadiyah Gombong - Ery Purwanti; Rina Yustika Devi; Yuli Susilowati (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2021)
Background: SARS-CoV-2 caused COVID-19. The Indonesian government introduced a distance-learning policy in mid-March 2020. Online learning is education that takes place over the internet and can be conducted in the home. Parents have to accompany their children many times at home, and it was impacted parent stress. Purpose: to know the relationship of study from home and parents stress level when they accompany their children during the COVID-19 pandemic. Method: This study was descriptive correlational research with a cross-sectional approach. The total respondents were sixty-six parents of students at SD Kreatif Muhammadiyah Gombong. They were recruited as respondents by random sampling technique. The structured instrument in this study was LORI and PSS-10. Result: From sixty-six respondents there were sixty-two women (93.9%), sixty-one aged 25-45 years old (92,4%), thirty-six had higher education background (54.5%), twenty-six were housewife (39.4%). A number of thirty-one respondents were at an adequate level (47%) when they accompanied their children to study at home, and fourth-one respondents were in high levels (62.1%). Analysis data used the Spearmen rank test, and it showed a relationship between both variables (p-value = 0.035 < 0.05). Conclusion: There was a relationship between study from home and parents stress level. Recommendation: This resulting study can be a reference for the parent who has students studying at home. The parent can also give motivation regularly, and it may improve children’ performance. Besides on the parent should have coping strategies to solve all problems.